Electronic Structure and Transport Properties of Superlattices: La(1-X)SrxTiO3 (X =0, 0.20, 0.80, 1) - Rai, R. K.; Kaphle, G. C.; Ray, R. B.; Niraula, O. P. (Journal of Nepal Physical Society, 2020)
The conventional density functional theory (DFT) and dynamical mean field theory (DMFT) is used to study the structural, electronic and the Mott-Hubbard metal-insulator phase transition of the pristine and superstructures, La(1-x)SrxTiO3 (x = 0, 0.20, 0.80, 1). The electrical and thermal conductivities, Seebeck coefficient, Figure of merit are calculated using the BoltzTraP codes. The present study reveals that the direct band gap of 2.20 eV and indirect band gap 2.0 eV at the Γ point in the Brillouin zone of SrTiO3 is upgraded to 3.423eV by using modified Beck-Johnson (mBJ) interaction potential. The metal-insulator transition (MIT) of LaTiO3 and the superlattice La(1-x)SrxTiO3 have been investigated by using conventional density functional theory (DFT) and dynamical mean field theory (DMFT). The Mott-Hubbard metal-insulator transitions for pristine LaTiO3 for a Coulombian parameter, U = 2.5 eV and the thermodynamic parameter β = 6 (eV)-1 are consistent with the experimental results. A typical set of these correlation parameters for MIT La0.20Sr0.80TiO3 and La0.80Sr0.20TiO3 systems are found to be U = 3.5 eV and β = 10(eV)-1 and U = 3.2 eV and β = 10 (eV)-1 respectively. The characteristic sharp quasi-particle peak for a sample of La0.80Sr0.20TiO3 superlattice systems is obtained correlation parameter U = 3.0 eV and β = 6(eV)-1. A thermoelectric phase transition is observed for Seebeck Coefficient at temperature 300 K at near chemical potential, μ = 1eV of SrTiO3. The corresponding figure of merit (ZT) with chemical potential (μ) appears to be unity at near μ = 1eV.